Shrinking cities, urban expansion, and air pollution in China: A spatial econometric analysis. (15th November 2021) - Qiang, Wei; Lin, Ziwei; Zhu, Pengyu; Wu, Kang; Lee, Harry F.
Abstract: Although shrinking cities' socio-economic sustainability has been focused in academia, the diffusing nature of shrinking cities' environmental impact has rarely been systematically investigated. It remains uncertain the spatial extent of the effect of shrinking cities has on the environment. In this study, we address this issue by calculating the concentration of PM2.5 in the built-up area of 640 prefecture-level and county-level cities in China, and applying the Spatial Dubin Model (SDM) to analyze the spatial relationship between shrinking cities, built-up area expansion, and air pollution in China between 2000 and 2016. Our statistical findings indicate a negative relationship between shrinking cities and increased air pollution, both directly and indirectly. When cities contract, the growth of air pollution in local and surrounding areas decreases by 0.143% and 0.635%, respectively. However, shrinking cities associated with urban built-up area expansion have relatively higher air pollution growth. They contribute 0.598% and 4.968%, respectively, to the increase in air pollution in the local and surrounding areas. Besides, local economic development in mitigating air pollution has a positive spatial spillover effect on air quality in the neighboring cities. In contrast, local population size has a negative spatial spillover effect. The above findings contribute knowledge to the convoluted spatial dynamics between urban decline and air pollution in China. The associated policy implications are also discussed. Graphical abstract: Image 1 Highlights: Precisely calculate the PM2.5 concentration in the built-up area of 640 prefecture/county-level cities in China. Apply spatial econometric models to trace the local and spatial spillover effect of shrinking cities on air pollution growth. When cities contract, air pollution growth in local and surrounding areas drops by 0.143% and 0.635%. Built-up area expansion in shrinking cities causes air pollution growth in local and surrounding areas by 0.598% and 4.968%.